Low-dose budesonide treatment for prevention of postoperative recurrence of Crohn's disease: a multicentre randomized placebo-controlled trial - Ewe, Klaus; Böttger, Thomas; Buhr, Heinz J.; Ecker, Karl-Wilhelm; Otto, Herwart F. (European journal of gastroenterology & hepatology, 1999)
Summary and Conclusion: Although the effect of budesonide was altogether positive in almost all variables studied in this train (e.g. endoscopic and histopathological score, time-to-failure, CDAI, patients' global judgement and rate of side effects), this increase in efficacy was small and the power for the detecting differences versus placebo was too low to be statistically significant. According to these results, low-dose oral budesonide cannot be recommended to be used for the prevention of postoperative relapse in Crohn's disease
Gesehen am 08.11.2017